Development and validation of an instrument to assess primary school students’ perceptions of the learning environment - Aldridge, Jill; Galos, S. (Springer, 2017)
© 2017 Springer Science+Business Media B.V. Over the past 40 years, numerous instruments have been developed to assess the learning environment for a variety of purposes. Despite this plethora of available surveys, there are few that have been developed for use at the primary school level, and even fewer that have been comprehensively validated. This article describes the development of a long-overdue learning environment survey that is suited to primary school students. Evidence to support the validity of the survey, in terms of translation and criterion validity, was guided by Trochim and Donnelly’s (2006) construct validity framework. A pilot test involving one class of 30 students and interviews with six students was used to examine the face validity of individual items. Analyses of data collected from 609 students in 31 classes supported the convergent, concurrent, discriminant and predictive validity, the results of which were all satisfactory. This article is significant in that it provides educators and researchers with a valid tool to assess the learning environment. The instrument, named the Classroom Climate Questionnaire—Primary (CCQ-P), is described and its practical advantages and limitations are discussed.